Reinventing the Model of Pesantren-Based Literary with the Insight of Religious Moderation - Mohammad Andi Hakim (The Institute of Research and Service Community IPMAFA Pati, 2021)
This study revealed the design of the model of pesantren-based literary with the insight of religious moderation and its contribution in strengthening religious moderation through education and writing training programs. Establishing literacy model of santri with a good scientific tradition and the contextual dialectic of thought is must be developed. Through the model developed as an effort to reinvent literature of pesantren with religious moderation values is able to become a reference for the design of santri writing training and its application in realizing Wasatiyyah Islam. This research is qualitative method with a descriptive qualitative approach. The data are collected through observation and documentation. The results of this study found two important things; First, the new model of pesantren-based literary with the insight of religious. Second, the contribution of pesantren-based literary model in realizing the agent of peace.